2017
DOI: 10.1017/s2040174417000824
|View full text |Cite
|
Sign up to set email alerts
|

The impact of periconceptional alcohol exposure on fat preference and gene expression in the mesolimbic reward pathway in adult rat offspring

Abstract: Alcohol consumption around the time of conception is highly prevalent in Western countries. Exposure to ethanol levels during gestation has been associated with altered development of the mesolimbic reward pathway in rats and increased propensity to addiction, however the effect of exposure only around the time of conception is unknown. The current study investigated the effects of periconceptional alcohol exposure (PC:EtOH) on alcohol and palatable food preferences and gene expression in the ventral tegmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
(67 reference statements)
1
22
0
Order By: Relevance
“…This was particularly evident in the second choice period, when the novelty of the new diet had presumably waned (Dorey et al . ). This was contrary to a recent study in rat offspring exposed to a higher dose of alcohol exclusively around conception, which found that males preferentially consumed more HFD than controls (Dorey et al .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This was particularly evident in the second choice period, when the novelty of the new diet had presumably waned (Dorey et al . ). This was contrary to a recent study in rat offspring exposed to a higher dose of alcohol exclusively around conception, which found that males preferentially consumed more HFD than controls (Dorey et al .…”
Section: Discussionmentioning
confidence: 97%
“…This was contrary to a recent study in rat offspring exposed to a higher dose of alcohol exclusively around conception, which found that males preferentially consumed more HFD than controls (Dorey et al . ). However, this study was conducted in much older rats (15 months of age).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations